The Mediating Role of Entrepreneurial Orientation in the Relationship Between Personal Traits and Firm Performance: Insights from Jaffna District - Tharshiga, P.; Thusalini, S.; Rathiranee, Y. (PGS Institute of Management / PGS College of Technology, 2025)
The research investigates the relationship between Entrepreneurial Psychological Capital (EPC) and Firm Performance Expectations (FPE), emphasizing the mediating role of Entrepreneurial Orientation (ENO). A quantitative study design was employed, utilizing convenience sampling to collect survey data from 90 entrepreneurs in the Jaffna District. Data analysis was performed using SPSS 22 and SmartPLS 4 software, implementing structural equation modeling through the partial least square’s method. The findings indicate that EPC exerts a direct influence on FPE, with variables such as achievement motivation, need for cognition, and internal locus of control identified as critical factors driving business success. Additionally, ENO was found to serve as a significant mediator between EPC and FPE. Entrepreneurs exhibiting personal attributes that encourage proactive, risk-taking, and innovative behaviors are more inclined to adopt an entrepreneurial orientation, thereby enhancing business performance. These results underscore the importance of cultivating robust personal characteristics and an entrepreneurial mindset among entrepreneurs to improve business outcomes. The study contributes to the literature by elucidating the direct impact of EPC on FPE and the essential mediating function of ENO. Moreover, it stresses the significance of nurturing both personal traits and entrepreneurial orientation to optimize business results. The contributions of the study highlight the dual influence of EPC on FPE, both directly and indirectly through ENO. Future research should consider incorporating diverse samples and employing objective measures of firm performance to further validate the proposed relationships.
Keywords: Need for achievement; Need for cognition; Internal locus of control; Entrepreneur orientation; entrepreneur‘s Characteristics and Firm Performance